A systematic review of in‐person versus remotely delivered interventions for youth with chronic pain - Nicole E. MacKenzie; Mica Gabrielle Marbil; Sabine Soltani; Diane L. Lorenzetti; Kathryn A. Birnie (Wiley, 2024)
Abstract The COVID‐19 pandemic prompted a rapid shift from in‐person to virtually‐delivered care. Many youth with chronic pain have the ability to access care virtually; however, little is known about the efficacy of pain care for youth with chronic pain delivered virtually when compared to in‐person. Such evidence is essential to guide youth in making decisions about their care, but also to inform what options health professionals present to youth. The purpose of this systematic review and meta‐analysis was to examine the efficacy of interventions that are delivered in‐person versus virtually for youth with chronic pain. Five databases (i.e., CINAHL, EMBASE, MEDLINE, APA PsycINFO, and Web of Science) were searched in October 2022 to identify randomized controlled trials that compare single/multimodal interventions for pediatric chronic pain delivered in‐person versus virtually. A total 3638 unique studies were identified through database and other searching, two of which satisfied established criteria for inclusion in this review. Both studies compared psychological interventions delivered virtually versus in‐person for youth with chronic pain and showed comparable efficacy across modalities. The planned meta‐analyses could not be conducted due to different outcomes within each study that could not be combined. This systematic review highlights a critical gap in the evidence regarding the efficacy of virtually delivered interventions for youth with chronic pain. This evidence is necessary to inform treatment decisions for youth, and further research is required to develop the evidence to inform clinical interventions, especially as virtual treatments continue to be offered.